Memberdayakan Pemikiran Komputasional melalui PBL-SSI: Menangani Ancaman Konservasi Secara Efektif - Nisa Sholehah Pangsuma; Widi Purwianingsih; Mimin Nurjhani Kusumastuti (Jurnal Penelitian Pendidikan IPA, 2025)
Computational thinking is one of the skills needed to support 21st-century skills, especially in science education, such as conservation biology. This study aims to analyze the increase in CT in conservation biology lectures, especially the topic of conservation threats. The lectures given are based on PBL-SSI. This study is a quantitative study with a quasi-experimental method. The research design used is a one-group pretest and posttest. The instrument used is a multiple-choice test with 15 questions containing indicators of computational thinking. The thinking indicators used consist of algorithms, decomposition, abstraction, and pattern recognition. The results show that PBL-SSI can significantly improve computational thinking skills with the decomposition indicator as the indicator that shows the most improvement